BCN nanosheets templated by g-C3N4 for high performance capacitive deionization - Wang, Shiyong; Wang, Gang; Wu, Tingting; Zhang, Yunqi; Zhan, Fei; Wang, Yuwei; Wang, Jigang; Fu, Yu; Qiu, Jieshan (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Capacitive deionization (CDI) is an emerging technology for removing charged ions from saline water and has attracted much attention in recent years. Developing a new electrode material with a reasonable structure is of great significance for obtaining high CDI performance. Herein, two-dimensional (2D) boron carbon nitride (BCN) nanosheets were fabricated using a new approach, which uses g-C3N4 as both the template and the nitrogen source, boric acid as the boron source and a subsequent pyrolysis process. The as-prepared BCN nanosheets show a pore structure with a high specific surface area and were investigated as CDI electrode materials for the first time. Moreover, the high heteroatom content, with a potential synergistic effect of N and B atoms, results in fast ion diffusion and good charge transfer ability. The BCN nanosheets demonstrate a high salt adsorption capacity of 13.6 mg g−1 at 1.4 V applied voltage when the initial NaCl concentration is 500 mg L−1. The BCN electrodes also exhibited better cyclic stability over 15 adsorption–desorption cycles. These results indicate that BCN nanosheets should be practicable candidates for high performance CDI electrode materials.